Differences between Patients Undergoing Laparoscopic Cholecystectomy with Discharge at the End of the Day Versus Overnight Stay: A Retrospective Study - Macedo-Alves, Daniela (2020)
Introduction: Although laparoscopic cholecystectomy is an increasingly performed technique in the outpatient setting, it is not done in some Units due to lack of overnight stay. The objectives of this study are to identify the differences between patients with discharge at the end of the day versus overnight stay and the factors predicting overnight stay.Material and Methods: A retrospective analysis of the pre, peri and postoperative data of patients operated between January/2014 and December/2017 was performed, and a statistical analysis of the variables.Results: A total of 311 patients were included, 33.4% of whom stayed overnight. Of these, 81.7% were operated after 2pm. As predictors factors of overnight stay, the age (p = 0.001) was identified in the morning group, with a greater possibility of overnight stay (15.3%) from 61.50 years (Younden index = 0.396) and the surgery start time (p < 0.0001) in the afternoon group, with a greater possibility of overnight stay (77.1%) from 4:30 pm (Younden index = 0.492).Discussion: Most patients stayed overnight due to the time at which recovery was completed, since no cause was identified (84.7%). If our unit would not have an overnight stay we would have an overall hospitalization rate of 8.4%, which corresponds to patients with an identified cause for overnight stay, and to admitted patients.Conclusion: Ambulatory cholecystectomy can be performed in units that cannot cater for an overnight stay, provided that surgeries are performed during the morning period, patients are carefully selected and there is the possibility of admission.